Pelatihan Pemanfaatan Spreadsheet untuk Meningkatkan Kompetensi Guru SMK Bisnis dan Manajemen dalam Menyusun Laporan Keuangan - Nayang Helmayunita; Ade Elsa Betavia; Dovi Septiari; Sany Dwita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Based on interviews conducted with the Head of the Vocational High School Management and Business Vocational High School Subject Teacher Conference in West Sumatra Province, it was found that teachers need to improve their competence about the use of Computer Accounting Applications. It is known that teachers still lack competence, and teachers are still unfamiliar with how to operate various menus and functions that can be used in a spreadsheet program to complete company financial reports. Based on this condition, the teaching and learning process for subjects has been done more with the lecture method and a little practice. So that this affects the competence of SMK graduates. In fact, the guidance for the world of work requires SMK graduates to operate this application program properly. The community's activity was carried out for two days on 18 and 19 September 2020 at SMKN 2 Kota Padang. The implementation is carried out in three stages, namely material presentation, integrated training, and evaluation. At the end of the activity, it was known that there was an increase in the understanding of the participants regarding the preparation of financial statements of trading companies using Microsoft Excel with a case settlement value that could be achieved was 85.71%. Furthermore, this increase in teacher competence is expected to be transferred to students and is reflected in the value of UKK and the acceptance of graduates in the world of work.